Value co-creation in the creative industry from the museum’ perspective - Sawczuk, Magdalena (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
Contacts with the environment, relations as well as different variants of value creation are more intensively explored. Issues of relations concern also museums, which modify their offers and cooperate with private entities, e.g. from the movie industry. However, value co-creation is more often referred to the final stage of the activities and the visitors, instead of other entities. The purpose of the study was to analyze the specificity of the co-creation realized by the museums and the movie industry. A case study method was used. Results showed that a separate movie realization has elements specific to the DART model and value co-creation. Despite some difficulties, through dialogue and interactions is possible to create value.